Long-Noncoding RNA ANCR Activates the Hedgehog Signaling Pathway to Promote Basal Cell Carcinoma Progression by Binding to PTCH - Wu H; He P; Xie D; Wang J; Wan C (Dove Medical Press, 2022)
Hongxuan Wu,* Pingxiu He,* Dong Xie, Jianqiao Wang, Chuan Wan Department of Dermatology, The First Affiliated Hospital of Nanchang University, Nanchang, 330006, People's Republic of China*These authors contributed equally to this workCorrespondence: Chuan Wan, Department of Dermatology, The First Affiliated Hospital of Nanchang University, Nanchang, 330006, People's Republic of China, Tel +86-791-88692799, Email chuanwan@ncu.edu.cnPurpose: The long non-coding RNA (lncRNA) anti-differentiation noncoding RNA (ANCR) is closely related to the occurrence and development of various malignancies. However, its expression and potential role in basal cell carcinoma (BCC) have not been established. In this study, we characterized the effects of ANCR in BCC and its underlying mechanism.Methods: The expression of ANCR in BCC tissues and cells was detected by qRT-PCR. Proliferation, invasion, migration and apoptosis of ANCR overexpressed or knock down TE354.T and A431 cells were examined by CCK8, transwell assay, wound healing assay and flow cytometry analysis, respectively. Western blot was performed to measure the expression of apoptosis-related proteins (BAX, BCL2 and Cleaved-caspase3), epithelial-mesenchymal transformation-related proteins (E-cadherin, N-cadherin, vimentin and β-catenin), and Hedgehog-pathway-related proteins (PTCH, GLI1 and SMO). RNA pull-down assay was used to analyze the relationship between ANCR and PTCH. The effect of ANCR on BCC growth in vivo was analyzed using xenograft model. TUNEL assay was used to determine the cell apoptosis.Results: ANCR and Hedgehog pathway were more highly expressed in BCC tissues than in adjacent normal tissues. ANCR overexpression substantially promoted BCC cell proliferation, invasion, and migration, inhibited apoptosis, and up-regulated BCL2 and decreased the expression of BAX and Cleaved-caspase3 proteins. Additionally, the upregulation of N-cadherin, vimentin, β-catenin, PTCH, GLI1, and SMO expression, and downregulation of E-cadherin expression were observed after ANCR overexpression. Moreover, ANCR knockdown had the opposite effects. An RNA pull-down assay further revealed that ANCR is specifically bound to PTCH. In vivo experiments also showed that ANCR overexpression significantly increased tumor growth and decreased apoptosis, which was reversed by cyclopamine, a specific inhibitor of the Hedgehog signaling pathway.Conclusion: ANCR activates the Hedgehog signaling pathway by binding to PTCH, thereby promoting BCC progression; accordingly, ANCR could be a candidate therapeutic target in BCC.Keywords: anti-differentiation noncoding RNA, basal cell carcinoma, Hedgehog signaling pathway, PTCH, epithelial-mesenchymal transition